Student teachers and their mentors: differing perspectives of the mentoring experience during initial teacher training in Ghana - Bawa Kuyini, Ahmed (2022)
This study explored student teachers’ (mentees) and their mentors’ perspectives of the mentoring during initial teach ing practice in Ghana. Guided by the framework of mentor as role model, peer support and sponsor, a 15-item question naire (Mentoring Support Scale) – premised on four factors – was combined with two open-ended questions to gather data. A total 321 student teachers (mentees) and their men tors participated in the study. Quantitative procedures (descriptive, t-tests, ANOVA) and qualitative procedures (the matic analysis) were used to analyse the data. The results showed that mentors rated themselves higher than student teachers (mentees) as providing more support in the mentor ing situation. Factor analysis confirmed the proposed four- factor model designed to measure the mentoring engage ment/relationship in Ghana. The challenges of the mentoring program include limited support, inadequate communica tion and feedback. How to address these issues are discussed with respect to preparation before teaching practice and the mentoring interactions in schools.